The radiological situation around the former uranium processing plant MAPE Mydlovary, Czech Republic - Havránková, Renata; Havránek, Jiří; Kaňkovský, Josef; Řepa, Libor; Zölzer, Friedo (Vinča Institute of Nuclear Sciences, 2015)
The uranium processing plant MAPE Mydlovary in South Bohemia, Czech Republic, was in operation for about 30 years from 1962 until 1991. Extensive remediation and reclamation work has been done in the area. In the study presented here we measured mass and volume activities of certain radionuclides in soil and water samples from the surroundings and measured gamma equivalent dose rates at the same locations. The average activity concentrations of 40K, 226Ra, a 238U in soil were 307.3 ± 4.4 Bq kg-1, 133.4 ± 0.8 Bq kg-1 and 113.2 ± 3.8 Bq kg-1, resp., whereas in water they were 5.7 ± 0.3 Bq l-1, 0.30 ± 0.03 Bq l-1 and 1.8 ± 0.16 Bq l-1, resp. The gamma equivalent dose rate at 5 cm and 1 m height above ground was 0.15 ± 0.04 µSv h-1 and 0.15 ± 0.03 µSv h-1, resp. As shown by comparison with the findings for similar sites elsewhere in the world, as well as with the results of measurements at uncontaminated locations, these values are compatible with regulation limits and there is no reason for concern regarding the radiation protection for workers involved with further remediation and reclamation, or carrying out other activities in the area.
Keywords: uranium; radium; activity concentration; gamma dose equivalent; radioecology